2023
DOI: 10.3390/insects14070613
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, Electrophysiological, and Toxicological Responses of Plutella xylostella to Extracts from Angelica pubescens

Abstract: Plutella xylostella L. is a destructive pest affecting cruciferous vegetables, causing massive economic losses worldwide. Plant−based insecticides are considered promising insect control agents. The Angelica pubescens extract inhibited female oviposition, with an oviposition deterrence index (ODI) of 61.65% at 12.5 mg/mL. We aimed to identify the bioactive compounds in A. pubescens extract. The compounds from A. pubescens extract were analyzed using LC−MS techniques. The toxicity and behavioral responses of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…It appears that there is an ideal range beyond which extremely high plant volatile chemical levels overwhelm receptors and may cause avoidance (Yang et al, 2004). While there are slight changes in attraction between married and virgin females, which are most likely related to physiological variances, both remain significantly stimulated by essential plant volatile chemicals (Zheng et al, 2023). This demonstrates the DBM olfactory systems' fine-tuned sensitivity to these key plant chemicals.…”
Section: Effectiveness Of Different Kinds Of Allelochemicals To Trap ...mentioning
confidence: 94%
“…It appears that there is an ideal range beyond which extremely high plant volatile chemical levels overwhelm receptors and may cause avoidance (Yang et al, 2004). While there are slight changes in attraction between married and virgin females, which are most likely related to physiological variances, both remain significantly stimulated by essential plant volatile chemicals (Zheng et al, 2023). This demonstrates the DBM olfactory systems' fine-tuned sensitivity to these key plant chemicals.…”
Section: Effectiveness Of Different Kinds Of Allelochemicals To Trap ...mentioning
confidence: 94%
“…6,7 What is more, Zheng et al demonstrated DMCA against adult and larval stages of Plutella xylostella. 8 In 2024, a study showed that DMCA had antiplatelet effects for both ADP and collagen and showed anticoagulant activities. 9 The practical application of chemical substances is always closely related to the interaction between the molecules in the system, and molecular interactions can determine its physical properties such as dissolution, crystal nucleation, and growth.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Medvedeva et al reported that DMCA is natural metabolites present in human blood, which can be the most promising therapeutical for synucleinopathies’ treatment . In addition, ferulic acids and various methylated cinnamic acid derivatives, like DMCA, improve cell viability and indirectly increase the expression of various endogenous antioxidant enzymes. , What is more, Zheng et al demonstrated DMCA against adult and larval stages of Plutella xylostella . In 2024, a study showed that DMCA had antiplatelet effects for both ADP and collagen and showed anticoagulant activities …”
Section: Introductionmentioning
confidence: 99%